2014
DOI: 10.1111/acps.12367
|View full text |Cite
|
Sign up to set email alerts
|

Sleep in patients with remitted bipolar disorders: a meta-analysis of actigraphy studies

Abstract: This meta-analysis of sleep in remitted bipolar disorder highlights disturbances in several sleep parameters. Future actigraphy studies should pay attention to age matching and levels of residual depressive symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
133
4
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 179 publications
(155 citation statements)
references
References 58 publications
9
133
4
3
Order By: Relevance
“…A recent meta-analysis of sleep actigraphy studies by Geoffroy et al [20] highlights significant differences between remitted bipolar patients and healthy control subjects in sleep latency, sleep duration, wake after sleep onset, and sleep efficiency that correspond with our results obtained by the BRIAN and SWPAQ scales. It should be also mentioned that, in some studies, a high correlation has been obtained between actigraphy measures and the CSM [21] and between the CSM and self-reported sleep-wake diaries [13,22].…”
Section: Discussionsupporting
confidence: 88%
“…A recent meta-analysis of sleep actigraphy studies by Geoffroy et al [20] highlights significant differences between remitted bipolar patients and healthy control subjects in sleep latency, sleep duration, wake after sleep onset, and sleep efficiency that correspond with our results obtained by the BRIAN and SWPAQ scales. It should be also mentioned that, in some studies, a high correlation has been obtained between actigraphy measures and the CSM [21] and between the CSM and self-reported sleep-wake diaries [13,22].…”
Section: Discussionsupporting
confidence: 88%
“…A recent meta-analysis of studies objectively estimating sleep variables in remitted BD patients demonstrated prolonged total sleep time (TST), increased wakenings after sleep onset and reduced sleep efficiency (4). This meta-analysis highlighted that there has also been little consistency in the way sleep and circadian rhythm has been measured and assessed.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, but specifically addressing BD, Abdullah et al evaluated the feasibility of inferring social rhythms in a sample of BD patients using automatically captured smartphone data. The authors found that solely relying on this kind of information it was possible to accurately predict social rhythm stability (De Crescenzo et al, 2017;Geoffroy et al, 2015;Scott et al, 2017). …”
Section: Discussionmentioning
confidence: 99%